Outcomes for Surgery in Stage IA Large Cell Lung Neuroendocrine Compared With Other Types of Non-Small Cell Lung Cancer: A Propensity Score Matching Study Based on the Surveillance, Epidemiology, and End Results (SEER) Database - Zou, Liqing; Guo, Tiantian; Ye, Luxi; Zhou, Yue; Chu, Li; Chu, Xiao; Ni, Jianjiao; Zhu, Zhengfei; Yang, Xi (Frontiers in Oncology, 2020)
Background Pulmonary large cell neuroendocrine cancer (LCNEC) is commonly classified as non-small cell lung cancer (NSCLC). Even for stage I disease, after surgery the survival is always poor, but clinical research on LCNEC is scant and always with unsatisfying sample sizes. Thus, we conduct the first study using the Surveillance, Epidemiology, and End Results (SEER) database to compare survival after surgery between stage I LCNEC and other types of NSCLC. Methods From 2004 to 2016，473 patients with stage IA LCNEC, 17669 patients with lung adenocarcinoma (LADC), and 8475 patients with lung squamous cell cancer (LSCC), all treated with surgery, were identified. 1:1 PSM was used, and overall (OS) and cancer-specific survival between groups were compared. Results The 5-year OS rates and CSS rates for LCNEC were 52.5% and 81.5%, respectively. Overall, both OS and CSS were significantly superior for stage IA LADC than LCNEC (for OS: HR 0.636, 95% CI 0.568-0.712; for CSS: HR 0.688, 95% CI 0.561-0.842, LCNEC as reference), while comparable for LSCC with LCNEC (for OS: HR 0.974, 95% CI 0.869-1.091; for CSS: HR 0.907, 95% CI 0.738-1.115). PSM generated 471 pairs when LCNEC was compared with LADC，and both OS and CSS were significantly better in LADC than LCNEC（for OS: HR 0.580, 95% CI 0.491-0.686; for CSS: HR 0.602, 95% CI 0.446-0.814）. Of note, for the subgroup of patients ≤ 65 years old，HRs for both OS and CSS were lower (for OS: HR 0.470; for CSS: HR 0.482). As for comparison between LCNEC and LSCC, PSM generated 470 pairs. Differently, only CSS was significantly superior in LSCC than LCNEC (HR 0.563, 95%CI 0.392-0.807), while OS wasn’t. Further grouping by age showed only CSS between two groups for patients with age≤65 years old was significantly different (P=0.006). Conclusions We report the first survival comparison after surgery between stage IA LCNEC and other types of NSCLC by SEER database and PSM. Our results demonstrated after surgery, stage IA LCNEC was worse in survival, especially compared to LADC. Extra clinical care should be paid, especially for younger patients. More studies investigating adjuvant therapy are warranted.